Juvenile Pityriasis Rubra Pilaris - Belliappa A.D; Bhat Ramesh M; Shetty J.N (Wolters Kluwer Medknow Publications, 2001)
A seven year old girl presented with erythematous, scaly, acuminate papules over the face, earlobes, chest, back, buttocks. Shoulders and limbs of ten months duration. Biopsy revealed hyperkeratosis, mild acanthosis and hypergranulosis in the epidermis, focal and perivascular infiltrate in the dermis, consistent with pityriasis rubra pilaris. Patient responded well to oral vitamin A and topical retinoids.